Medical education and population health—A framework in the design of a new undergraduate program - Armstrong, Robert W.; Mantel, Michaela; Walraven, Gijs; Atwoli, Lukoye; Ngugi, Anthony K. (Frontiers in Public Health, 2022)
Health sciences curricular planners are challenged to add new content to established education programs. There is increasing pressure for content in public health, health systems, global health, and planetary health. These important areas often compete for curricular time. What is needed is a convergence model that builds a common framework within which students can integrate areas and better align this knowledge to the individual client or patient who they have responsibility to support. A population health framework is proposed for health sciences education programs that supports a common conceptual understanding of population health. The framework links five thematic areas that have influence on health and wellbeing and a sixth element that defines the range of methodologies essential to understanding health and wellbeing, from the individual to the population. The five areas providing convergence are: (1) the biopsychosocial development of the individual, (2) the socioeconomic factors that influence health and wellbeing, (3) the physical natural and built environment including climate, (4) the continuum of public health and health care systems, and (5) the nation state and global relationships. Using this framework, students are encouraged to think and understand individual health and wellbeing in context to the population and to utilize the appropriate methodological tools to explore these relationships. Planning for a new undergraduate medicine program illustrates the curricular elements that will be used to support student learning with foundation knowledge applied and tracked throughout the program. The proposed framework has application across health sciences disciplines and serves to build a common understanding that supports cross professional communication and collaboration.